The nexus between Capital Structure, profitability, and environmental performance: empirical evidence from Indonesia - Sunita Dasman; Ananto Tri Sasongko; Widiastuti; Gilbert Alexander Saputra; Ida Jubaedah (Jurnal Akuntansi Bisnis Pelita Bangsa, 2025)
This study investigates the nexus between capital structure, profitability, and environmental performance among companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The objective is to analyze how financial leverage and environmental performance influence profitability, as well as the mediating role of profitability in linking capital structure to environmental performance. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on 126 companies, the results show that capital structure negatively affects profitability and environmental performance, while environmental performance positively influences profitability. Profitability significantly mediates the relationship between capital structure and environmental performance, supporting both the Trade-Off and Stakeholder Theories. The findings emphasize the need for firms to maintain optimal leverage and integrate sustainability strategies to enhance long-term profitability and corporate value.